Social innovation and “other” knowledges: what does the construction of formal knowledge have to do with it? - Ferreira, Marcia Regina; Fleig, Daniel Gustavo (Revista Campo-Território, 2024)
By examining the intersection of sexism and racism in the university, we seek to reflect on the construction of knowledge and how this formal space of knowledge creation can contribute not to reproduce and repeat offered models, but rather build an “other” education. It is argued that the educational context cannot be analyzed without considering the project of modernity, coloniality, racialization, and violence in our country. After all, this coloniality is also present in the university. Starting from this colonial legacy of the knowledge structure (epistemic racism/sexism), the coloniality of power (domination and asymmetry in relationships), and understanding its implications in university life, this essay aims to address decoloniality and to think about social innovations through the valorization of marginalized knowledge (“other” bodies), in order to reflect upon what does formal knowledge construction have to do with it. As a result, the fissures in the Eurocentric wall produced through social innovations and other knowledges are presented, highlighting the contributions and challenges of formal knowledge in Brazil. With fundamental elements such as interculturality, decolonization, and decoloniality, the essay indicates that in recent decades universities have become a space for announcing and denouncing social, cognitive, and relational injustices. This change is occurring through the emergence of new configurations of educational institutions in Brazil. Finally, this feeling-thinking [sentir-pensar] about education is considered as a social innovation, as it presents new praxis that articulate love, pedagogy, humanities, and liberation, as found in critical interculturality and the biopraxis of Latin American education.